(untitled) (Revista Apotheke, 2024)
The article proposes to think about intersectionality as a way to understand how social inequalities of gender and race are mutually constituted, especially based on the authors’ experiences both in the field of teaching in Visual Arts and in the critical and contextualized articulation of the relationship between culture and human development, as well as its transdisciplinary connections. In this sense, the methodological place followed the paths of the teaching experience from a critical and reflective perspective on the formative, cultural and identity aspects. Thus, intersectionality, as a tool, awakened multiple voices, to understand and reflect on the role and place of enunciation of black feminism, considering the possible openings outlined as a project and pedagogical proposal.